1995
DOI: 10.2527/1995.731166x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of copper level on nutrient utilization of weanling pigs.

Abstract: The effect of addition of 15 or 250 ppm of Cu (as CuSO4.5H2O) and 0 or 5% added animal fat on the utilization of nutrients by weanling pigs was evaluated. Two trials were conducted with four groups of four littermate barrows (6.8 kg, 26 d) in each trial. Dietary treatments were arranged in a 2 x 2 factorial. Data were collected at the beginning of the trial and at the end of each 3-d period. There were no treatment x period interactions (P > .15). There was a Cu level x fat level interaction for ADG (P < .01),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
28
4
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 0 publications
9
28
4
4
Order By: Relevance
“…In the current study, ADG, ADFI and F/G were improved during the first two weeks and over the entire experimental period. The supplementation of copper improved both piglet growth performance and apparent digestibility of protein, fat, calcium, and phosphorus and these findings are in good agreement with a previous studies in which high dietary copper levels improved animal growth and digestibility of nutrients (Dove, 1995). Piglets fed diet with 250 mg/kg -1 copper may improve the activities of digestive enzymes (Luo and Dove, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, ADG, ADFI and F/G were improved during the first two weeks and over the entire experimental period. The supplementation of copper improved both piglet growth performance and apparent digestibility of protein, fat, calcium, and phosphorus and these findings are in good agreement with a previous studies in which high dietary copper levels improved animal growth and digestibility of nutrients (Dove, 1995). Piglets fed diet with 250 mg/kg -1 copper may improve the activities of digestive enzymes (Luo and Dove, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, EE digestibility was increased with increasing dietary Cu levels. Similar results were reported in pigs (Dove 1995;Luo and Dove 1996) and in Black Bengal kids (Datta et al 2007). Luo and Dove (1996) reported that the addition of 250 mg/kg Cu improved digestibility and utilization of fat in weanling pigs.…”
Section: Discussionsupporting
confidence: 86%
“…Luo and Dove (1996) reported that the addition of 250 mg/kg Cu improved digestibility and utilization of fat in weanling pigs. The improvement in apparent fat digestibility due to Cu addition (more than 48 mg/kg) observed in the present study and the previous study may also be partially due to increased lipase and phospholipase A activities in the small intestine (Dove 1995;Luo and Dove 1996). Moreover, Cu functions biochemically as a component of several Cu-dependent enzymes and as a co-factor for numerous other enzymes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Apparent digestibility values for Cu, Fe, and Zn during each collection phase were calculated according to the procedures outlined by Dove (1995):…”
Section: Measurementsmentioning
confidence: 99%